Conversion of glycerol to hydroxyacetone over SrTiO3 -type perovskite: A DFT study - Ignacio Lizana (Elsevier, 2021)
Glycerol is currently a co-product of biodiesel production, and it is well-known to be a platform molecule, which is widely used in etherification, dehydration, dehydrogenation, oxidation, and reforming reactions, to produce chemicals of high value for the chemical industry. In this study, we theoretically address the dehydration of glycerol over the SrTiO3-type perovskite. The study includes the characterization of the transition states and intermediates occurring along the reaction pathway, and a possible mechanism is proposed, as well. The results show that the dehydration of glycerol occurs via a four-stage mechanism corresponding to the adsorption of glycerol on the perovskite, the surface reaction to produce the adsorbed dihydroxyacetone, the elimination of water produce 2,3-enol, and finally the desorption of this enol, which in turn undergoes keto-enol tautomeric equilibrium to form hydroxyacetone (HA). The rate-limiting stage corresponds to the formation of 2,3-enol showing an activation barrier of 106.3 kcal/mol.